Training for Increasing Ability to Calculate Profit Loss in Entrepreneurship for MSMEs Tegal Alur: Pelatihan Peningkatan Kemampuan Menghitung Laba Rugi Dalam Berwirausaha Bagi UMKM Tegal Alur - Vinola Herawaty; Ayu Aulia Oktaviani; Rukmini Windiarti Soebadio (Yayasan Ahmar Cendekia Indonesia, 2022)
This activity aims to provide knowledge and understanding of financial calculations in entrepreneurship, especially profit and loss calculations. The target participants are MSME entrepreneurs in the Tegal Alur Village area, West Jakarta. Most of their line business is a home-based business which generally sells snacks to culinary delights and souvenirs and several businesses wedding equipment rental. The method of activity is counseling and training using prepared materials and question and answer discussion session. This training was carried out on February 2, 2022 in collaboration between MSMEs in the Tegal Alur Village Area and the Faculty of Economics and Business, Trisakti University. The results obtained by the participants were able to calculate the profit and loss from the business, so that it had an impact on their ability to assess performance and make decisions to develop their business. Abstrak Kegiatan ini bertujuan memberikan pengetahuan dan pemahaman perhitungan keuangan dalam berwirausaha khususnya perhitungan laba rugi. Target peserta yaitu pengusaha UMKM di wilayah Kelurahan Tegal Alur, Jakarta Barat. Rata-rata bidang usaha mereka yaitu usaha rumahan yang pada umumnya menjual makanan kecil hingga kuliner dan cinderamata dan beberapa usaha penyewaan peralatan pernikahan. Metode kegiatan yaitu penyuluhan dan pelatihan menggunakan materi yang dipersiapkan dan sesi diskusi tanya jawab. Pelatihan ini terlaksana pada 2 Februari 2022 atas kerjasama antara UMKM Wilayah Kelurahan Tegal Alur dengan Fakultas Ekonomi dan Bisnis Universitas Trisakti. Hasil yang diperoleh yaitu para peserta mampu menghitung laba rugi usahanya, sehingga berdampak pada kemampuannyamenilai kinerja dan pengambilan keputusan keuangan usahanya.